Microstructural, Mechanical and Thermal Characteristics of Recycled Cellulose Fiber-Halloysite-Epoxy Hybrid Nanocomposites - Alamri, Hatem; Low, It Meng (Wiley Interscience, 2012)
Epoxy hybrid-nanocomposites reinforced with recycled cellulose fibers (RCF) and halloysite nanotubes (HNTs) have been fabricated and investigated. The dispersion of HNTs was studied by synchrotron radiation diffraction (SRD) and transmission electron microscopy (TEM). The influences of RCF/HNTs dispersion on the mechanical properties and thermal properties of these composites have been characterized in terms of flexural strength, flexural modulus, fracture toughness, impact toughness, impact strength, and thermogravimetric analysis. The fracture surface morphology and toughness mechanisms were investigated by SEM. Results indicated that mechanical properties increased because of the addition of HNTs into the epoxy matrix. Flexural strength, flexural modulus, fracture toughness, and impact toughness increased by 20.8, 72.8, 56.5, and 25.0%, respectively, at 1 wt% HNTs load. The presence of RCF dramatically enhanced flexural strength, fracture toughness, impact strength, and impact toughness of the composites by 160%, 350%, 444%, and 263%, respectively. However, adding HNTs to RCF/epoxy showed only slight enhancements in flexural strength and fracture toughness. The inclusion of 5 wt% HNTs into RCF/epoxy ecocomposites increased the impact toughness by 27.6%. The presence of either HNTs or RCF accelerated the thermal degradation of neat epoxy. However, at high temperature, samples reinforced with RCF and HNTs displayed better thermal stability with increased char residue than neat resin.